2014
DOI: 10.1002/2014gl061357
|View full text |Cite
|
Sign up to set email alerts
|

Tropical to extratropical: Marine environmental changes associated with Superstorm Sandy prior to its landfall

Abstract: Superstorm Sandy was a massive storm that impacted the U.S. East Coast on 22-31 October 2012, generating large waves, record storm surges, and major damage. The Coupled Ocean-Atmosphere-Wave-Sediment Transport modeling system was applied to hindcast this storm. Sensitivity experiments with increasing complexity of air-sea-wave coupling were used to depict characteristics of this immense storm as it underwent tropical to extratropical transition. Regardless of coupling complexity, model-simulated tracks were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Observations from the glider showed that downwelling-favorable winds limited the supply of cold bottom water to be mixed upward as Sandy approached (Figure 7). The glider observations also showed that surface cooling was limited to 1°C-2°C (Zambon et al, 2014), contributing only slightly to the weakening of Sandy over the continental shelf. In the aftermath of Hurricane Sandy, the multi-institutional TEMPESTS (The Experiment to Measure and Predict East coast STorm Strength) program was initiated to collect ocean observations for improved intensity forecasts of storms impacting the US northeast using moorings, ALAMO floats, and gliders.…”
Section: Alps-enabled Improvements In Tc Ocean-induced Dynamics and Imentioning
confidence: 89%
“…Observations from the glider showed that downwelling-favorable winds limited the supply of cold bottom water to be mixed upward as Sandy approached (Figure 7). The glider observations also showed that surface cooling was limited to 1°C-2°C (Zambon et al, 2014), contributing only slightly to the weakening of Sandy over the continental shelf. In the aftermath of Hurricane Sandy, the multi-institutional TEMPESTS (The Experiment to Measure and Predict East coast STorm Strength) program was initiated to collect ocean observations for improved intensity forecasts of storms impacting the US northeast using moorings, ALAMO floats, and gliders.…”
Section: Alps-enabled Improvements In Tc Ocean-induced Dynamics and Imentioning
confidence: 89%
“…Other capabilities, including an atmospheric model, are available in this coupled system and have been used to investigate Hurricane Sandy atmosphere -ocean dynamics (Zambon et al, 2014a(Zambon et al, , 2014b. This series of applications, however, utilized a set of atmospheric surface forcings (described below) and ran the other model components to focus on the oceanographic and wave response during the storm.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…These in turn modify the atmospheric processes and feedback to the ocean and wave dynamics. Model coupling has been shown: 1) to increase predictability of sea surface temperatures for simulating Hurricane Isabel (2003;Warner et al, 2010); 2) the effects of waves to increase the sea surface roughness thus creating reduced wind speeds and producing more accurate atmosphere -ocean dynamic during Nor'Ida (2009;Olabarrieta et al, 2012); 3) to provide more accurate intensity predictions for Hurricane Ivan due to sea surface temperature feedbacks Zambon et al, 2014a); 4) that there was a lack of significant ocean feedback on the hurricane intensity dynamics for Hurricane Sandy because of its fast translation speed (2012; Zambon et al, 2014b); and 5) the significance of air-sea exchanges during extratropical cyclones (Nelson et al, 2014) and coastal storm events (Renault et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kossin (2018) indicates that the average translation speed for NIO storms is in the range of 3.5-4 mÁs −1 . Owing to these factors, the underestimation of the simulated storm-induced cooling can be mainly attributed to the limitation of the OML model, which can be rectified by coupling with a 3D ocean model (Zambon et al, 2014b;Prakash and Pant, 2017).…”
Section: Storm-induced Ocean Responsementioning
confidence: 99%
“…To replace the OML, several studies on the application of sophisticated atmosphere–ocean coupled models for the TC cases have indicated the impact of oceans on the atmosphere, and vice versa (e.g. Warner et al ., ; ; Zambon et al ., , 2014b). For the BOB, the recent TC simulation study by Prakash et al .…”
Section: Introductionmentioning
confidence: 99%